Pengaruh Jumlah Dewan Komisaris, Leverage, Profitabilitas, Intensitas Modal, Cash Flow, Dan Ukuran Perusahaan Terhadap Konservatisme (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2017) - Suharni, Siti; Wildaniyati, Arini; Andreana, Dea (Universitas Merdeka Madiun, 2019)
This study is aimed at examining the effects of the Number of Board of Commissioners, Leverage, Profitability, Capital Intensity, Cash Flow, and Company Size toward Conservatism in the manufacturing companies listed on the Indonesian Stock Exchange (IDX). The population used in this study is the yearly financial statements on firm of manufacturing listed at BEI period 2012-2017, using purposive sampling method. The type of data used is secondary data obtained from yerly financial reports published and downloaded through the official BEI website. Data analyzed with Descriptive statistics, test of classic assumption and exmination of hypothesis with multiple linier regression method. The result of hypothesis research shows variable Profitability and Cash Flow have a significant effect on the ability of Conservatism, while the Number of Board of Commissioners, Leverage, Capital Intensity, and Company Size has no effect on the ability of Conservatism.